Molecular Cloning and Characterization of Dmc1 from the Chinese Mitten Crab (Eriocheir sinensis) - Yuan Liu; Zhaoxia Cui (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2015)
Dmc1, a member of the RecA/Rad51 super family, is essential for meiotic recombination. In this study, a Dmc1 gene (EsDmc1) was identified from screening the larval transcriptomes of Chinese mitten crab Eriocheir sinensis. The full-length cDNA of EsDmc1 was 1478 bp long and contained a 1026 bp open-reading frame encoding 341 amino acids. The genomic fragment of EsDmc1 contained two exons separated by one intron. Several tandem repeats were found in intron. The deduced EsDmc1 protein contained motifs conserved in the RacA/Rad51 superfamily, including the Walker A and B motifs, and L1 and L2 loops. EsDmcl shared 87.3%, 86.5% and 77.4% identity with its homologues in Litopenaeus vannamei, Penaeus monodon and Ixodes scapularis, respectively. Phylogenetic analysis revealed that EsDmc1 had a closer relationship with Dmc1s from arthropods than vertebrates. The EsDmcl transcripts could be detected in all examined larval stages with the highest expression level in the fifth zoeal stage. These results suggest that EsDmc1 could be expressed before  reproductive maturity and might have complex functions in crab reproduction.